אפעל, י״, הנוודים בספת ארץ״ישראל בתקופת האימפריות האשורית, הבבלית והפרסית - Eph‛al, Israel (1971)
The Nomads on the Border of Palestine in the Assyrian, Babylonian and Persian Periods; Thesis submitted for the degree “Doctor of Philosophy”; I. The Akkadian and Biblical Sources: II. Historical Survey.